Безопасность гидротехнических сооружений на водохранилищах беларуси: структура базы данных - Levkevich Виктор; Malashevich Валерий; Lasuta Геннадий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The structure (main clauses) of the data base, which provides decisions regarding the handling of hydraulic structures with artificial water bodies in Belarus is submitted in this article.